Perubahan Tutupan Lahan pada DAS Bendung Kota Palembang dengan Metode NDVI - Vionadwiuchtia Idrat; Indrayani Indrayani; Akhmad Mirza; Tata Prayoga; Azzahra Ramadhanti; M. Rama Miftah Wijaya; Prasetya Ardhana (Universitas Batanghari Jambi, 2026)
Rapid urban development to accommodate population growth has led to significant land use changes. The Bendung Watershed, located in Palembang City, is one of the areas with a high potential for flooding. Several factors contribute to flooding in Palembang, including inadequate drainage system performance, extensive swamp reclamation over the years, low-lying topography, and land use changes. Land cover change is one of the factors affecting flood discharge; therefore, this study aims to analyze land cover changes in the Bendung Watershed using the Normalized Difference Vegetation Index (NDVI) method based on Landsat remote sensing imagery from 2005 and 2024. The research methodology included watershed boundary delineation using DEM SRTM data, processing of Landsat imagery through geometric and radiometric corrections, band composite generation, NDVI transformation, land cover classification, and classification accuracy assessment. The results indicate that between 2005 and 2024, the built-up area increased by 21.15%, while open space and water bodies decreased by 40.98% and 36.89%, respectively.